2019
DOI: 10.21203/rs.2.9493/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Premedication with dexmedetomidine to reduce emergence agitation: a randomized controlled trial

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This may be due to the higher dose (0.5-4 μg/kg) and the more uniform route (transnasal or oral) of DEX administration in the premedication subgroup, leading to a more consistent DEX effect in reducing the incidence of EA. Preoperative administration of DEX has been shown to have several significant benefits, including a lower incidence of EA, reduced agitation severity, and a shorter duration of agitation (94). Therefore, high-quality evidence supports preoperative DEX administration to prevent EA in children.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the higher dose (0.5-4 μg/kg) and the more uniform route (transnasal or oral) of DEX administration in the premedication subgroup, leading to a more consistent DEX effect in reducing the incidence of EA. Preoperative administration of DEX has been shown to have several significant benefits, including a lower incidence of EA, reduced agitation severity, and a shorter duration of agitation (94). Therefore, high-quality evidence supports preoperative DEX administration to prevent EA in children.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and network meta-analysis investigated which medications' relative e cacies on decreasing emergence cough after general anesthesia, the result found dexmedetomidine ranked more effective than lidocaine, remifentanil and fentanyl in reducing moderate to severe cough reponse [17]. Kim et al found a calm state at emergence in the group receiving dexmedetomidine compared with that receiving placebo for nasal bone fracture surgery [18]. A meta-analysis including 19 randomized controlled trials concluded that dexmedetomine signi cantly reduced the incidence of agitation and severe pain during recovery period [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, anesthesiologists have been striving to reduce the incidence of EA and improve the quality of patient's postoperative condition with the help of various drugs and techniques. Several drugs such as remifentanil (9), magnesium sulphate (5) and dexmedetomidine (1,10,11) have been suggested as potential prophylactic interventions of EA in adult patients. However, little progress has been made in therapeutics.…”
Section: Introductionmentioning
confidence: 99%